RETORIKA KEPRESIDENAN DAN KECEMASAN GEOPOLITIK (ANALISIS KOMUNIKASI FILOSOFIS ATAS DISKURSUS PRESIDEN AMERIKA SERIKAT TERHADAP IRAN SERTA RESONANSINYA DI CINA, KOREA UTARA, DAN TIMUR TENGAH) - Herman Herman (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT Escalating political rhetoric in relations between the United States and Iran illustrates that presidential communication functions not merely as a vehicle for conveying foreign policy, but also as a mechanism for shaping international perceptions of threats, legitimacy, and the geopolitical order. Against this backdrop, this study explores how the rhetoric of the President of the United States produces political meaning and generates discursive resonance across China, North Korea, and the Middle East from the perspective of the philosophy of communication. The research adopts a qualitative approach within a critical interpretive paradigm and employs Norman Fairclough’s Critical Discourse Analysis enriched by Michel Foucault’s power/knowledge perspective. Data were collected from official presidential speeches, policy documents, diplomatic statements, and international media coverage, and were analyzed through the stages of textual analysis, discursive practice, and social practice, supported by source triangulation and cross-checking across documents. The analysis identifies five major themes: the construction of threat narratives toward Iran, the representation of military power as a source of political legitimacy, the formation of geopolitical identities through processes of subjectivation, the normalization of uncertainty as a political communication strategy, and the emergence of discursive resonance interpreted differently by international actors according to their respective strategic interests. These findings demonstrate that presidential rhetoric does not merely represent international political dynamics; rather, it actively constructs threat perceptions, produces geopolitical knowledge, and influences the orientation of global political communication through the discursive operation of power/knowledge. ABSTRAK Meningkatnya intensitas retorika politik dalam hubungan Amerika Serikat dan Iran memperlihatkan bahwa komunikasi kepresidenan tidak hanya berfungsi menyampaikan arah kebijakan luar negeri, tetapi juga berperan dalam membentuk persepsi internasional mengenai ancaman, legitimasi, dan tatanan geopolitik. Atas dasar itu, penelitian ini mengeksplorasi bagaimana retorika Presiden Amerika Serikat memproduksi makna politik serta menghasilkan resonansi wacana di Cina, Korea Utara, dan kawasan Timur Tengah melalui perspektif filsafat komunikasi. Penelitian menerapkan pendekatan kualitatif dengan paradigma interpretive kritis serta menggunakan Critical Discourse Analysis Norman Fairclough yang diperkaya perspektif power/knowledge Michel Foucault. Data dihimpun dari pidato resmi Presiden Amerika Serikat, dokumen kebijakan, pernyataan diplomatik, dan pemberitaan media internasional, kemudian dianalisis melalui tahapan analisis teks, praktik diskursif, praktik sosial, serta diperkuat dengan triangulasi sumber dan cross-checking antardokumen. Analisis menghasilkan lima tema utama, yaitu narasi ancaman terhadap Iran, representasi kekuatan militer sebagai sumber legitimasi politik, pembentukan identitas geopolitik melalui praktik subjektivasi, normalisasi ketidakpastian sebagai strategi komunikasi politik, serta resonansi wacana yang dimaknai secara beragam oleh aktor internasional sesuai kepentingan strategis masing-masing. Temuan tersebut menegaskan bahwa retorika kepresidenan tidak sekadar merepresentasikan dinamika politik internasional, melainkan turut membentuk konstruksi ancaman, memproduksi pengetahuan geopolitik, dan memengaruhi orientasi komunikasi politik global melalui mekanisme power/knowledge yang bekerja secara diskursif.